Water Birth – Benefits, Risks, and Controversies - Górny, Julia; Kapciak, Alicja; Naja, Katarzyna; Zwardoń, Jakub; Hawajski, Artur; Jankowska, Natalia; Kamieniecka, Oliwia; Świerzyńska, Adrianna; Mazur, Weronika; Pawelec, Natalia (Quality in Sport, 2025)
Introduction: Water birth, involving immersion in water during childbirth, has gained popularity for its potential benefits, such as pain relief and comfort. While widely practiced in some countries, concerns regarding its safety, particularly for neonates, remain. This paper explores the maternal and fetal benefits and risks associated with water birth, as well as the epidemiological trends, medical protocols, and legal considerations. Aim of Study: The aim of this study is to evaluate the maternal and neonatal outcomes of water immersion and water birth, focusing on the safety, efficacy, and factors influencing its adoption in different populations. Material and methods: A comprehensive review of the literature on water birth including its benefits, risks and controversies was performed using the PubMed database. Results and Conclusions: Water immersion during labor is associated with significant maternal benefits, including reduced pain and anxiety, shorter labor, and fewer pharmacological interventions. Water birth, however, carries potential risks, such as neonatal respiratory complications and infections, although studies generally report no significant differences in neonatal outcomes compared to land birth. Epidemiological trends show higher water birth rates among women aged 30–39, while socioeconomic factors, such as deprivation, are linked to lower rates. Water birth has been shown to reduce the incidence of severe perineal tears and postpartum hemorrhage. While promising, the practice requires careful adherence to medical protocols to ensure safety, with further research needed to fully establish its long-term benefits and risks.